Mihail Manoilescu – Inspirational Even when He Is Not Right - Ion Pohoata (Theoretical and Applied Economics, 2007)
Mihail Manoilescu is part of the series of those economists criticized in different ways, from the exaggeratedly appreciatively reviews to those that do not recognize any of his merits. The success of an analysis to place him where he rightfully belongs is related to taking into consideration a criterion –that of historical time in which Mihail Manoilescu formed himself as a state man and a science man. Only like this, only when thinking about the inter-war period, of great creative effervescence, of real renaissance for Romania, of affirmation and consolidation of the economy and of the Romanian state, of his imposing in the world economy, we can understand better the logic of his starting premises and of his judgments he based his theory on.